2013
DOI: 10.1177/0957926513482067
|View full text |Cite
|
Sign up to set email alerts
|

Pro-anorexia: Extensions of ingrained concepts

Abstract: Pro-anorexia is an internet-based movement that hails eating disorders as a lifestyle choice. This article aims to reveal pro-anorexia members' underlying conceptualisations of anorexia that contribute to the maintenance of the disorder. Cognitive linguistic analysis was undertaken on a corpus of data collected from systematically selected pro-anorexia websites. The findings show that the members structure their eating disorder experiences through two central conceptual metaphors: ANOREXIA IS A SKILL and ANORE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
(50 reference statements)
0
37
0
Order By: Relevance
“…We then expect those groups to have similar habits of communication and accentuate their similarities. For example, research on pro-ana websites has found that individuals categorize themselves based on their weight, space, social interactions and dedication to perfection (Figueras Bates, 2015;Knapton, 2013). Additionally, studies on the fat acceptance movement indicate that members tend to categorize themselves as an "autonomous, self-transparent and self-authoring community" (Murray, 2005, p. 275).…”
Section: Social Identity and Body Imagementioning
confidence: 99%
“…We then expect those groups to have similar habits of communication and accentuate their similarities. For example, research on pro-ana websites has found that individuals categorize themselves based on their weight, space, social interactions and dedication to perfection (Figueras Bates, 2015;Knapton, 2013). Additionally, studies on the fat acceptance movement indicate that members tend to categorize themselves as an "autonomous, self-transparent and self-authoring community" (Murray, 2005, p. 275).…”
Section: Social Identity and Body Imagementioning
confidence: 99%
“…Then there are no further decisions to make." This interaction between self and goddess "Ana" could be viewed as the realization of the conceptual metaphor ANOREXIA IS A RELIGION, identified by Knapton (2013) as one fundamental key conceptualization in the pro-ana movement.…”
Section: The Social Selfmentioning
confidence: 99%
“…In the linguistic level, some differences between the words used for self-presentation in proeating disorders and recovery sites have also been established (Lyons et al, 2006;Wolf et al 2007 and. In the discursive level, Knapton (2013) and Figueras (2015) has highlighted some fundamental metaphors in pro-ana websites and online groups that define the pro-ana identity. More recently, researchers have focused on how pro-ana discourses are projected in image-based platforms such as Instagram (Ging & Garvey 2018) to reify the ideal pro-ana self.…”
Section: Identity In Pro-ana Websitesmentioning
confidence: 99%